2002
DOI: 10.1159/000048333
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Electroretinogram with a Multiflash Stimulation Technique in Open-Angle Glaucoma

Abstract: Purpose: To analyze a multiflash multifocal electroretinogram in 20 patients with open-angle glaucoma (OAG). Methods: The stimulation sequence consisted of a binary m-sequence (Lmax 200 cd/m2, Lmin <1 cd/m2). Each m-sequence stimulus was followed by three global flashes (luminance: 400 cd/m2) at an interval of 26 ms. Results: The presence of a response to the three global flashes indicated an adaptive effect of the response to the preceding m-sequence stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 18 publications
0
41
0
1
Order By: Relevance
“…279 This stimulus results in a direct response due to focal flash and an induced response due to interaction of focal and global flash and was proposed to enhance responses from the ganglion cell and the optic nerve head component (ONHC). 63,222,282 It was shown that diabetic patients without retinopathy had significantly lower amplitude in the induced component, whereas the direct response was similar compared with controls without diabetes. 281 The application of this multifocal stimulus with periodic global flash may enable early detection of retinal dysfunction in diabetic patients.…”
Section: Diabetic Retinopathymentioning
confidence: 98%
See 2 more Smart Citations
“…279 This stimulus results in a direct response due to focal flash and an induced response due to interaction of focal and global flash and was proposed to enhance responses from the ganglion cell and the optic nerve head component (ONHC). 63,222,282 It was shown that diabetic patients without retinopathy had significantly lower amplitude in the induced component, whereas the direct response was similar compared with controls without diabetes. 281 The application of this multifocal stimulus with periodic global flash may enable early detection of retinal dysfunction in diabetic patients.…”
Section: Diabetic Retinopathymentioning
confidence: 98%
“…63,222,289 Techniques which have been employed to enhance these components included insertions of three successive global flashes or alternating dark and global flashes in between the multifocal stimuli. 63,222,281 Palmowski et al demonstrated that patients with POAG had reduction in the nasal retinal response amplitude to the second of the three global flashes compared with control. 222 The clinical application, however, is limited because many of the POAG patients still had amplitudes within normal limits.…”
Section: Focal Laser and Pan-retinal Photocoagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings showed that interposing bright global flashes into the stimulation sequence increased the inner retinal contributions to the mfERG and therefore its sensitivity in glaucoma. With the use of 3 global flashes, the sensitivity to detect glaucomatous dysfunction was 50 % [10]. One single global flash increased the sensitivity to 75 % and the specificity to 83 %.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found significant differences between glaucoma and control when the bandpass filter was set at 10-300 Hz [7]. Applying the same filter setting, the sensitivity of the mfERG to detect glaucomatous retinal dysfunction was increased when global flash paradigms were introduced [10,11].…”
Section: Introductionmentioning
confidence: 99%